Caractériser les liens entre qualification et gestion des ressources : une analyse comparative d’instruments de gestion des végétations en élevage - Nathalie Girard; Antoine Doré; Danièle Magda (Développement Durable et Territoires)
Building on a domain in which the valuation of resources used in agricultural production systems is at the core of debates on their management, the objective of this article is to provide a comparative analysis of valuation instruments, in order to characterize the links between valuation and management of natural resources. With a managerial and sociological analysis of three instruments valuating semi-natural vegetation used in livestock systems, we show how they describe the vegetation, the flock and the farmer, assigning them roles and skills. We explore how they prescribe different management modes of these vegetations, thus calling for various management philosophy. This analysis invites to take a look, not on the intrinsic value of these resources, but on how these instruments establish contrasting « practical meanings » of the notion of resource.